Mechanism of fibroblast growth factor 21 in cardiac remodeling - Zhao, Zeyu; Cui, Xuemei; Liao, Zhangping (Frontiers in Cardiovascular Medicine, 2023)
Cardiac remodeling is a basic pathological process that enables the progression of multiple cardiac diseases to heart failure. Fibroblast growth factor 21 is considered a regulator in maintaining energy homeostasis and shows positive roles in preventing damage caused by cardiac diseases. This review mainly summarizes the effects and related mechanisms of fibroblast growth factor 21 on pathological processes associated with cardiac remodeling, based on a variety of cells of myocardial tissue. The possibility of Fibroblast growth factor 21 as a promising treatment for the cardiac remodeling process will also be discussed.